Radiography-based score indicative for the pathogenicity of bacteria in odontogenic infections. (October 2014) - Cachovan, Georg; Blessmann, Marco; Schön, Gerhard; Rother, Uwe; Heiland, Max; Stürenburg, Enno; Platzer, Ursula; Sobottka, Ingo
Abstract Objective. To develop a new radiography-based score to assess the potential of bacteria to cause odontogenic infections derived from the occurrence of bacteria at small or large radiographical lesions. Materials and methods. The patients analyzed were a sub-population from a large randomized clinical trial comparing moxifloxacin and clindamycin in the treatment of inflammatory infiltrates and odontogenic abscesses. Routine radiographs were used to analyze the area of the periapical radiolucent lesions. Lesions were stratified by their radiographically measured area as large (>9 mm2) or small (≤9 mm2). A risk ratio was calculated for each species from the frequency of their occurrence in large vs in small lesions. Results. Fifty-one patients, 19 with abscesses and 32 with infiltrates, were evaluated. Overall, the radiographical lesion areas ranged from 0.4–46.2 mm2 (median = 9 mm2). An increased risk (risk ratio >1) to occur at large abscess lesions was observed for Prevotella (P.) oralis, P. buccae, P. oris, P. intermedia, Fusobacterium nucleatum and Streptococcus (Strep.) anginosus group. An increased risk to occur at large infiltrate lesions was found for Strep. salivarius, Strep. parasanguis, Strep. anginosus group, Capnocytophaga spp., Neisseria (N.) sicca, Neisseria spp., Staphylococcus(Staph.)aureus, P. intermedia, P. buccae, Prevotella spp. and P. melaninogenica.Conclusions. The radiography-based score suggests that certain Prevotella spp., F. nucleatum and Strep. anginosus groups play a crucial role in the pathogenesis of odontogenic abscesses, and that various streptococci, Neisseria spp., Capnocytophaga spp., Staph. aureus and Prevotella spp. are involved in the pathogenesis of odontogenic infiltrates.